2010
DOI: 10.1073/pnas.0912613107
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution of energy metabolism genes and the origin of flight in bats

Abstract: Bat flight poses intriguing questions about how flight independently developed in mammals. Flight is among the most energyconsuming activities. Thus, we deduced that changes in energy metabolism must be a primary factor in the origin of flight in bats. The respiratory chain of the mitochondrial produces 95% of the adenosine triphosphate (ATP) needed for locomotion. Because the respiratory chain has a dual genetic foundation, with genes encoded by both the mitochondrial and nuclear genomes, we examined both gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
233
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(246 citation statements)
references
References 54 publications
9
233
0
4
Order By: Relevance
“…However, the false-positive rate found by those authors (20) was lower than the significance level (5%) (21). The branch-site test has been successfully applied in many studies, generating interesting biological hypotheses that have been validated by experimentation (22)(23)(24). In this study, 7 of 10 amino acids in SAS-B and 8 of 12 in AFPIII detected under positive selection (Table 1) showed hydrophobicity or charge switches from the corresponding sites of their paralogs or the precursor, implying biochemical property or activity changes.…”
Section: Resultsmentioning
confidence: 96%
“…However, the false-positive rate found by those authors (20) was lower than the significance level (5%) (21). The branch-site test has been successfully applied in many studies, generating interesting biological hypotheses that have been validated by experimentation (22)(23)(24). In this study, 7 of 10 amino acids in SAS-B and 8 of 12 in AFPIII detected under positive selection (Table 1) showed hydrophobicity or charge switches from the corresponding sites of their paralogs or the precursor, implying biochemical property or activity changes.…”
Section: Resultsmentioning
confidence: 96%
“…This might occur because of the metabolic demands of flight that could result in a more rapid increase in a higher mean strength of selection on bat mitochondria with increasing N e . There is some evidence to support this possibility: for example, there are signs of adaptive mitochondrial evolution on the common ancestral lineage of bats, but not rodents (Shen et al, 2010). In addition, Shen et al (2009) have found a relationship between flight ability and the strength of selective constraint in bird mitochondrial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Artifacts from the multiple-sequence alignment (PRANK 84,85 ) were trimmed by the Gblocks program 86 . After trimming, any alignment that was shorter than 100 bp was discarded 87 . To exclude variation in individual species, only amino acid changes shared by the three high-altitude snub-nosed monkey species were used.…”
Section: Methodsmentioning
confidence: 99%